PEMENUHAN HAK ANAK DALAM BUKU SISWA KELAS LIMA SEKOLAH DASAR KURIKULUM 2013 - Wahdan Najib Habiby; ika candra sayekti (Profesi Pendidikan Dasar, 2016)
The aim of this research was to investigate whether students’ text book Grade 5 Theme I in Curriculum 2013 has been fulfill child right in learning process or not. It was library research through qualitative approach, and using descriptive analytic method. The result of this study showed that Indonesian government has consistently applied the 1989 UN children right convention result, both juridically and applicatively. It can be seen on students’ text book Grade V Theme I Curriculum 2013 which has been fulfill child right but it is required to be actualized more in real learning process by the teacher.